PERBANDINGAN KURIKULUM DI BERBAGAI NEGARA BERKEMBANG PASCA PANDEMI COVID-19 - Jefril Rahmadoni; Saifaldin Idris Onia; Nova Asvio; Wiji Aziiz Hari Mukti; Hanura Febriani; Raveenthiran Vivekanantharasa (UIN Imam Bonjol Padang, 2023)
The Covid-19 pandemic that hit a few years ago, forced the education sector to change the learning system from face-to-face to online. Now with the end of the epidemic, learning is again being carried out face-to-face. This research will try to examine curriculum comparisons in various developing countries after the Covid- 19 pandemic. The research method used is a literature study. The results of his research are that some countries have changed their curricula after the Covid-19 pandemic, but some countries have not changed their curricula.